KOMUNIKASI INSTRUKSIONAL INSTRUKTUR DI LINDZ YOGA STUDIO PEKANBARU - Ahmad, Dang Syaras; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Yoga is one of the sports or physic exercises which is most wanted and popular nowadays. Yoga combines or unites mind, body and soul only by doing movements (asana) along with breathing technique and meditation. Yoga is lead by an instructor who gives the instruction for the members. In giving the instruction, the instructor uses instructional communication in doing exercise process. The purpose of this research is to know the instructional method, instructional communication media, and the communication obstacles which happen in Yoga exercise process.This research belongs to quantitative research method by using symbolic approach. The informants of this research were 3 instructors and 3 members at Lindz Yoga studio Pekanbaru, while the object of this research was the instructor’s instructional communication at Lindz Yoga studio Pekanbaru. The data collection technique was used by observation, interview and documentation. In order to get data validity in this research, the researcher used the extension of participation and triangulation.The result of this research showed that the instructor’s instructional communication to the members in doing Yoga exercise used three instructional communications, such as command method, exercise method and question answer method. The media that used were audio media, aids media and picture media. The most use media and also effective in the usage are audio and aids media. The obstacles which happened in instructional communication are the source’s obstacle, the channel’s obstacle, the communicant’s obstacle and psychological obstacle. Instructor as the communicator used verbal and nonverbal in the activity of instructional communication.Keyword : Yoga, instructional communication, Lindz Yoga studio Pekanbaru